Low adherence to hemodialysis regime in patients with chronic renal disease in a Peruvian Ministry of Health reference hospital - Herrera Añazco, Percy (2014)
Background: Failing to attend a monthly session within a scheme of conventional dialysis may increase mortality by 30%. Objectives: To describe the frequency and perceived causes of non-adherence to dialysis in a Peruvian national reference public hospital. Design: Descriptive study. Setting: Nephrology department, Hospital Nacional 2 de Mayo, Lima, Peru. Participants: Patients with more than one year on dialysis. Interventions: The number of absences to appointed sessions was determined and a validated questionnaire was used to describe perceptions regarding the causes of absences. Main outcomes measures: Low adherence to dialysis defined as patients with more than one absence per month or more than 12 absences between July 2012 and July 2013. Results: The study included 54 patients, of which 27 were male. Average age was 57 ± 16.4 years and average time on dialysis was 40.6 ± 11.5 months. Only 7 patients had higher education. There were 504 absences (5.45%). The second day of the weekly schedule was the day with more absences (292), followed by the third day (145). Overall 13 patients showed low adherence. Main causes of absence reported included a remote residence (6/13), feeling good (6/13), and insufficient financial resources to cover transportation costs (5/13). Conclusions: A quarter of patients had low adherence, being distance to health facility and wellbeing self-perception the main factors.